The effect of irrigation frequency on growth, flowering and stomatal conductance of osteospermum 'Denebola' and New Guinea impatiens 'Timor' grown on ebb·and-flow benches - Jadwiga Treder; Joanna Nowak (Acta Agrobotanica, 2013)
The response of osteospermum 'Denebola' and New Guinea impatiens 'Timor' grown on ebb-and-flow benches to different water potential of growing medium applied during whole growing period was investigated by measuring plant growth parameters and stomatal conductance (gS). After cutting establishment, four different irrigation treatments based on soil water potential were applied to osteospermum: at -0,5 , -3,0 , -10,0 , -20 kPa. In the case of impatiens the last water treatment was omitted. Plants were evaluated when they reach one ofthe three growth stages: lateral shoots development, visible flower buds (osteospermum) or beginning of flowering (impatiens) and at flowering. All plants produced with a moderate water deficit (irrigation at -3 and -10 kPa) were more compact than plants irrigated at -0,5 kPa but their flowering were not affected. Strong decrease in pIant growth and flowering was observed when plants were irrigated at the lowest water potential (-20 kPa). However, for impatiens the highest irrigation frequency was also not favorable. As a result of water stress the decrease in stomatal conductance (g~) in both plants was observed. Osteospermum was more resistant to water stress than impatiens.